2002
DOI: 10.1186/1475-2875-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to Plasmodium falciparum erythrocyte membrane protein-1: use of relatively conserved synthetic peptide pools to determine CD4 T cell responses in malaria-exposed individuals in Benin, West Africa

Abstract: BackgroundPlasmodium falciparum erythrocyte membrane protein-1, a variant antigen of the malaria parasite, is potentially a target for the immune response. It would be important to determine whether there are CD4 T cells that recognise conserved regions. However, within the relatively conserved region, there is variation. It is not possible to test T cell responses from small field samples with all possible peptides.MethodsWe have aligned sequences that are relatively conserved between several PfEMP1 molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Additionally, the passive transfer of IgG from highly exposed individuals (HEI) to non-immune patients could confer a protective effect to clinical symptoms of malaria [ 8 - 10 ]. Among proteins supposed to induce a protective immunity, the surface-expressed P. falciparum erythrocyte protein 1 (PfEMP-1) have been largely studied [ 11 - 13 ]. However, others erythrocytic parasite stage proteins were reported to elicit an immune response [ 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the passive transfer of IgG from highly exposed individuals (HEI) to non-immune patients could confer a protective effect to clinical symptoms of malaria [ 8 - 10 ]. Among proteins supposed to induce a protective immunity, the surface-expressed P. falciparum erythrocyte protein 1 (PfEMP-1) have been largely studied [ 11 - 13 ]. However, others erythrocytic parasite stage proteins were reported to elicit an immune response [ 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the use of synthetic peptides representing conserved sequences of PfEMP1 might be of value in determining regions of the molecule recognised by T cells of a wide variety of donors exposed to different variants of PfEMP1 [9]. The synthetic peptide sequences overlapped in some extent to the sequences predicted by antigenic sites and B cell epitopes by us.…”
Section: Discussionmentioning
confidence: 95%
“…The linear epitope carried by a synthetic peptide can induce antibodies that will protect mice against Semliki forest virus [55]. Some peptides have already been shown to be good immunogens [56], inducing strong T cell response. All these studies show that there is a real interest to design peptides as vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%